Public-private partnerships: Contract design and risk transfer - Mathias Dewatripont; Patrick Legros (EIB Papers, 2005)
This paper critically assesses the implications of contract design and risk transfer on the provision of public services under public-private partnerships (PPPs). Two results stand out. First, the alleged strength of PPPs in delivering infrastructure projects on budget more often than traditional public procurement could be illusory. This is - to put it simply - because there are costs of avoiding cost overruns and, indeed, cost overruns can be viewed as equilibrium phenomena. Second, the use of external (i.e., third-party) finance in PPPs, while bringing discipline to project appraisal and implementation, implies that part of the return on efforts exerted by the private-sector partner accrues to outside investors; this may undo whatever beneficial effects arise from 'bundling' the construction and operation of infrastructure projects, which is a hallmark of PPPs.
Keywords: 330; Public-Private Partnership; Infrastrukturinvestition; Vertragstheorie; Investitionsrisiko; Theorie